Entering The ESG Era And Carbon Business Opportunities: A Literature Review Of The Role Of Strategic Management Accounting In The Sustainability Transition In Indonesia - Fredy Rizaldi; Fabryan Suhandi; Yanuar Ramadhan (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The transformation towards a low-carbon economy encourages companies to align their business strategies with sustainability principles, including ESG integration and participation in carbon trading. This study aims to explore the role of strategic management accounting (SMA) in supporting the sustainability transition, particularly through the integration of emissions reporting, ESG strategy, and utilization of carbon business opportunities in Indonesia. This study uses a systematic literature review approach by analyzing 20 journals and professional reports published in the period 2020–2024. The results of the study indicate that SMA has the potential to be an information system that can bridge reporting compliance, environmental performance evaluation, and carbon-based strategic decision making. This study offers an initial conceptual model that simultaneously connects SMA, ESG, and carbon trading and identifies gaps in the literature and reporting practices in Indonesia. These findings provide conceptual contributions to the development of sustainability research and serve as a strategic reference for companies in adopting an adaptive business approach to climate pressures and green regulations.